2016
DOI: 10.1186/s40623-016-0524-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of close conjunctions between dayside polar cap airglow patches and flow channels by all-sky imager and DMSP

Abstract: Recent imager and radar observations in the nightside polar cap have shown evidence that polar cap patches are associated with localized flow channels. To understand how flow channels propagate from the dayside auroral oval into the polar cap, we use an all-sky imager in Antarctica and DMSP (F13, F15, F16, F17 and F18) to determine properties of density and flows associated with dayside polar cap patches. We identified 50 conjunction events during the southern winter seasons of 2007-2011. In a majority (45) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
4
10
0
Order By: Relevance
“…In the noon sector or the central polar cap, the convection speed is lower than in the dawn/dusk region (before 9 and after 17 MLT) around 80° MLAT (Figure b). After comparing the averaged IMF and convection speed data for each patch (Figures S2 and S3), and consistent with Wang et al (), the patch occurrence rate is higher near the polar cap boundary (around 80° MLAT) where there is larger convection speed for strongly negative IMF B y . The field‐aligned current is higher near 80° MLAT than in the central polar cap (>85° MLAT), and it is downward in the postnoon sector and upward in the prenoon sector (Figure c), which may be associated with the region 0 cusp current system (Iijima & Potemra, ).…”
Section: Observations and Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In the noon sector or the central polar cap, the convection speed is lower than in the dawn/dusk region (before 9 and after 17 MLT) around 80° MLAT (Figure b). After comparing the averaged IMF and convection speed data for each patch (Figures S2 and S3), and consistent with Wang et al (), the patch occurrence rate is higher near the polar cap boundary (around 80° MLAT) where there is larger convection speed for strongly negative IMF B y . The field‐aligned current is higher near 80° MLAT than in the central polar cap (>85° MLAT), and it is downward in the postnoon sector and upward in the prenoon sector (Figure c), which may be associated with the region 0 cusp current system (Iijima & Potemra, ).…”
Section: Observations and Resultssupporting
confidence: 88%
“…They found that some of airglow patches are associated with enhanced polar cap flow, strong localized filed‐aligned currents, and low‐energy precipitation. For large negative IMF B y , the airglow patch near the polar cap boundary can be associated with very fast antisunward flow (>~1,500 m/s; Wang et al, ). Recently, Zhang et al () used DMSP F16 in situ measurements to identify a similar enhanced density structure (electron density 6.6 × 10 5 cm −3 at 860‐km altitude) in the topside F region polar cap.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 shows that the flow channels were mostly between 200 and 300 km in latitudinal width with peak velocities of 1.1–1.3 km s −1 . The width values are of a similar order to previous studies, such as Pinnock et al (1993) (100 km), Provan et al (1998) (250 km), Wang et al (2016) (300 km), and Zou et al (2015) (200–300 km).…”
Section: Discussionsupporting
confidence: 84%
“…As stated, the look direction of the SuperDARN Longyearbyen radar could be biasing these results, as it is orientated in a favorable direction to detect zonal flow channels. However, Wang et al (2016) also find that they detect flow channels associated with airglow patches most frequently during IMF By dominant conditions. In that study, satellite data were used to determine the flow characteristics, removing the look direction bias that applies to single SuperDARN radars and still noting the same IMF By dependence.…”
Section: Discussionmentioning
confidence: 99%
“…The imager uses a single detector in conjunction with a special dual‐wavelength interference filter with two narrow passbands corresponding to each wavelength. The ASC captures one image every minute and has a 10 km geographic resolution over most of the field of view and sensitivity of 20 Rayleighs per 8 s of exposure [ Wang et al, ]. The mapping height used in our analysis for 630.0 nm is 230 km, while it is 110 km for 427.8 nm, and the images use arbitrary intensity scaling from 0 to 255.…”
Section: Instrumentation and Methodsmentioning
confidence: 99%